2019
DOI: 10.3390/ijerph16101709
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise on Glucoregulatory Hormones: A Countermeasure to Human Aging: Insights from a Comprehensive Review of the Literature

Abstract: Hormones are secreted in a circadian rhythm, but also follow larger-scale timetables, such as monthly (hormones of the menstrual cycle), seasonal (i.e., winter, summer), and, ultimately, lifespan-related patterns. Several contexts modulate their secretion, such as genetics, lifestyle, environment, diet, and exercise. They play significant roles in human physiology, influencing growth of muscle, bone, and regulating metabolism. Exercise training alters hormone secretion, depending on the frequency, duration, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 119 publications
2
17
0
Order By: Relevance
“…Aging is associated with the gradual decreasing in physiological reserves, an increased risk of comorbidities and mortality, and a general decline in the functional capacity associated with biological and external factors (Kirkwood, 2005;Sellami et al, 2019;Sepúlveda-Loyola et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Aging is associated with the gradual decreasing in physiological reserves, an increased risk of comorbidities and mortality, and a general decline in the functional capacity associated with biological and external factors (Kirkwood, 2005;Sellami et al, 2019;Sepúlveda-Loyola et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additional potential mechanisms of chronic exercise-induced benefits on sleep include reduction of inflammation, increases in growth hormone, alterations in autonomic function/heart rate variability, and changes in neurotransmitters important for sleep regulation. 16,17,37,38 In light of the prevalence of sleep dysfunction, mood disorders, autonomic dysfunction, and neuroinflammation in PD, the influence of exercise may be particularly relevant for this patient population. 1,39 In comparing objective sleep outcomes in the untrained state (baseline) with chronic and acute effects of exercise, sleep architecture was improved with CEX compared with baseline, whereas the same effects were not seen with AEX.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is unclear whether these findings translate to older adults or those with more severe metabolic abnormalities. A recent review involving three studies showed that regular exercise resulted in negligible effects on GH in older adults (Sellami et al, 2019 ). As the studies included in the review were limited to small samples and did not include stand-alone aerobic exercise interventions, further research is required to determine whether exercise-induced changes in physiologic GH improve age- and obesity-related disease in elderly cohorts.…”
Section: Aerobic Exercisementioning
confidence: 99%